2021
DOI: 10.1080/08897077.2021.1971818
|View full text |Cite
|
Sign up to set email alerts
|

Article Commentary: Physical Therapists Should Play a Greater Role in Managing Patients with Opioid use and Opioid Misuse

Abstract: The U.S. opioid crisis necessitates that health care providers of all types work collaboratively to manage patients taking prescription opioid medications and manage those who may be misusing prescription opioids. Musculoskeletal conditions are the most common diagnoses associated with an opioid prescription. Physical therapists commonly manage patients with musculoskeletal conditions and chronic pain. Some patients who attend physical therapy for pain management take prescription opioid medications for pain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…13 We recommend that PTs routinely monitor their patients opioid dose throughout an episode of physical therapy care. 9 Our nationwide survey of physical therapists indicates that 70.0% of physical therapists report that they never or rarely ask their patients about a history of opioid misuse. 11 Routine monitoring of patients in physical therapy should also include assessing for opioid misuse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 We recommend that PTs routinely monitor their patients opioid dose throughout an episode of physical therapy care. 9 Our nationwide survey of physical therapists indicates that 70.0% of physical therapists report that they never or rarely ask their patients about a history of opioid misuse. 11 Routine monitoring of patients in physical therapy should also include assessing for opioid misuse.…”
Section: Discussionmentioning
confidence: 99%
“…8 PTs, primary care providers (PCPs), addiction treatment leaders and scholars advocate that PTs should play a greater role screening and addressing patients with opioid misuse. 9,10 Indeed, in our prior work, we found that more than 89% physical therapists agree that they should play a role in managing patients with opioid misuse. 11 In the American Physical Therapy Association’s Standards of Practice for Physical Therapy, the functions of the physical therapist examination include identifying both physical therapy needs and other health needs of the patient or client.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…All health care providers play an important role 82 . Initiation of physical therapy has been associated with a reduction in opioid use.…”
Section: Team Approach: Role-specific Interventionmentioning
confidence: 99%